Improving performance and stability in quantum dot-sensitized solar cell through single layer graphene/Cu2S nanocomposite counter electrode. (January 2020) - Akman, Erdi; Altintas, Yemliha; Gulen, Mahir; Yilmaz, Mucahit; Mutlugun, Evren; Sonmezoglu, Savas
Abstract: In this work, we presented an effective nanocomposite to modify the Cu2 S film by employing single layer graphene (SLG) frameworks via chemical vapor deposition, and utilized this nanocomposite as counter electrode (CE) with CdSe/ZnS core/shell quantum dots for highly stable and efficient quantum dot-sensitized solar cell (QDSSC). Furthermore, Cu2 S film is directly synthesized on SLG framework by electrodeposition method. Using this nanocomposite as CE, we have achieved the high efficiency as high as 3.93% with fill factor of 0.63, which is higher than those with bare Cu2 S CE (3.40% and 0.57). This remarkable performance is attributed to the surface area enhancement by creating nanoflower-shape, the reduction of charge transfer resistance, improvement of catalytic stability, and the surface smoothness as well as good adhesion. More importantly, no visible color change and detachment from surface for the Cu2 S@SLG nanocomposite was observed, demonstrating that the SLG framework is critical role in shielding the Cu2 S structure from sulphur ions into electrolyte, and increasing the adhesion of the Cu2 S structure on surface, thus preventing its degradation. Consequently, the Cu2 S@SLG nanocomposite can be utilized as an effective agent to boost up the performance of QDSSCs. Highlights: Developing a one-step, highly stable, and electrocatalytically active Cu2 S@SLG composite CE on FTO substrate. A remarkably high PCE of 3.93% and FF of 0.63 for CdSe/ZnS core/shell quantum dots based solar cells. Excellent photostability under continuous operation. Passivating from the corrosive effect of the polysulfide electrolyte.